LEKSIKON ARSITEKTUR HIJAU DALAM BAHASA KAILI: PEMANFAATAN KEARIFAN LOKAL GREEN ARCHITECTURE LEXICON IN KAILI LANGUAGE: UTILIZATION OF LOCAL WISDOM - Deni Karsana (Balai Bahasa Sulawesi Tengah, 2019)
This study aims to reveal the lexicons in the Kaili etnic architecture as an effort to protect their ethno-architectural lexicons (houses). Remember the fundamental nature of the house as a necessity for human life, the local wisdom embedded in the Kaili house building reflects the concept of green architecture. This is an inseparable part of the fact that the language and culture of the houses in the Kaili etnics live, namely Palu, Sigi and Donggala as areas that often occur in earthquakes (Palu-Koro strike-slip fault ). Local knowledge that becomes local wisdom that carries the green architecture concept needs to be preserved. This reflects the value of local wisdom that is environmentally sound by upholding customs for the preservation of human civilization. The disclosure of this lexicon is done using a qualitative descriptive method. Language data in the form of lexicons of house buildings were analyzed to explore the description of Kaili etnics houses, their socio-cultural functions, and the concept of green architecture as disaster mitigation efforts. The findings of this study are expected to be able to strengthen research related to disaster mitigation (earthquake) in an interdisciplinary perspective to minimize the impact of disasters on human life.